Crosstalk between the microbiota and insect postembryonic development. Issue 2 (February 2023) - Girard, Maxime; Luis, Patricia; Valiente Moro, Claire; Minard, Guillaume
Abstract : Insect sequential development evolves from a simple molt towards complete metamorphosis. Like any multicellular host, insects interact with a complex microbiota. In this review, factors driving the microbiota dynamics were pointed out along their development. Special focus was put on tissue renewal, shift in insect ecology, and microbial interactions. Conversely, how the microbiota modulates its host development through nutrient acquisition, hormonal control, and cellular or tissue differentiation was exemplified. Such modifications might have long-term carry-over effects on insect physiology. Finally, remarkable microbe-driven control of insect behaviors along their life cycle was highlighted. Increasing knowledge of those interactions might offer new insights on how insects respond to their environment as well as perspectives on pest- or vector-control strategies. Highlights: Insects represent at least 70% of animal species and play a pivotal role for the functioning of ecosystems. Some species are also considered as major pests or pathogen vectors. Understanding the involvement of microbes in the hormonal balance regulation during the post-embryonic development might contribute to further applications for pest and vector management. It was noticed that the developmental strategy could drastically contribute to the stability of host microbial communities along the development. However, there is a lack of comparable datasets to fully integrate these results in a meta-analysis study. Many examples found the interconnection between nutritional symbiosis and the endocrine response of insects. It is believed that fluxomic investigations involving labeled substrates are currently lacking to help decipher the interconnection between these pathways.